Rancang Bangun Prototype Sistem Keamanan Sepeda Motor Transmisi Manual Berbasis Kombinasi Elektro Mekanik: Development of an Electromechanical Combination-Based Security System Prototype for Manual Transmission Motorcycles - Bayu Angga; Nyoman Arya Wigraha; I Gede Wiratmaja (Universitas Pendidikan Ganesha, 2026)
Motor vehicle theft remains a frequent problem in Indonesia. Many older motorcycles, particularly manual transmission vehicles manufactured before 2007, still use standard security systems such as handlebar locks, which have several weaknesses and can be manipulated by thieves. This research aims to develop a prototype security system for manual transmission motorcycles based on an electromechanical combination that can provide additional protection for the vehicle. This research employed a Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). The research stages included needs analysis, prototype design, product development, and feasibility testing through validation by instrument content experts, design experts, and manufacturing experts. Data was collected using questionnaires and documentation, then analyzed using quantitative descriptive analysis techniques. The results of the study indicate that the prototype electromechanical-based motorcycle security system was successfully developed. The instrument content expert validation obtained a validity score of 1, categorized as very high. The design expert feasibility test obtained a 100% rating, categorized as very feasible, while the manufacturing expert test obtained a 100% rating, categorized as very feasible. Based on these results, the prototype of a manual transmission motorcycle security system based on an electro-mechanical combination is declared suitable for use as an additional security system. Keywords : electromechanical, prototype, motorcycle security system, manual transmission, 4D development.